First we use sin(a+b)= sinacosb+sinbcosa
and cos(a+b)=cosa cosb -sinasinb
tan(x+pi/2)= sin(x+pi/2) / cos(x+pi/2)
and sin(x+pi/2) = sinxcospi/2 + sinpi/2cosx =cosx,
<span>cos(x+pi/2) = cosxcospi/2- sinxsinpi/2= - sinx,
</span> because <span>cospi/2 =0, </span>and <span>sinpi/2=1
</span><span>=tan(x+pi/2)= sin(x+pi/2) / cos(x+pi/2)= cosx / -sinx = -1/tanx = -cotx
</span>from where <span>tan(x+pi/2)=-cotx</span>
Answer:
ku hgkjfghdehfv bfd
Step-by-step explanation:
Answer:19/2
Step-by-step explanation:
19/2=9.5
Other are not in its very simplest form